2004
DOI: 10.1590/s0101-31222004000200018
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed bank variation patterns according to environmental factors in a natural grassland

Abstract: -This research aimed to determine the soil seed bank and its relationship with environmental factors that have an influence in the distribution of the vegetation above the ground in an excluded area of natural grassland in the South of Brazil. Most of the 122 identified species in the seed bank were perennials. Data analysis indicated three distinct community groups, according to the size and composition of the soil seed bank in lowlands with permanent wet soils, in lowlands and in other areas. In general, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
2
15
1
5
Order By: Relevance
“…Maia et al (2004), studying weed seed bank in natural fields observed that soil moisture content was the most imporant abiotic factor affecting patterns of vegetation variation. Other authors also consider soil water content as a determinant factor affecting weed seed bank germination (Munhoz & Felfili, 2006;Vivian et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maia et al (2004), studying weed seed bank in natural fields observed that soil moisture content was the most imporant abiotic factor affecting patterns of vegetation variation. Other authors also consider soil water content as a determinant factor affecting weed seed bank germination (Munhoz & Felfili, 2006;Vivian et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous factors affect weed seed germination including variations in soil temperature and moisture (Begum et al, 2006;Hérault & Hiernaux, 2004;Maia et al, 2004), light intensity (Vivian et al, 2008;Batlla & Benech-Arnold, 2014) and physiological aspects of the seeds particularly seed dormancy (Baskin & Baskin, 2006). When favorable environmental conditions occur and physiological constraints are overcome, seeds germinate; weeds grow and produce new propagules enriching the soil seed bank.…”
Section: Introductionmentioning
confidence: 99%
“…In the greenhouse, our seeds were protected from predators and systematically irrigated, which did not happen in the field. Maia et al (2004), studying weed seed banks in natural fields, also observed that soil moisture content was one the most important abiotic factors affecting the patterns of vegetation. Other authors have also cited soil water content as a determinant of weed seed bank germination (Munhoz & Felfili 2006;Vivian et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…[19] reported that the number of weed seeds in the soil ranged from 17,300 to 646,000 m −2 in New South Wales, Australia, Ref. [15] reported that in the top 5 cm of soil ranged from 52.1 to 167,000 seeds m Differences in the number of seeds or weed seedling density in the seedbank can be explained by several factors, including climate, relief position, soil moisture content, depth of sampling, history of the areas and management practices used by rice farmer [40].…”
Section: Weed Seedbank Size In Rice Fieldsmentioning
confidence: 99%
“…Various factors affect weed seed germination including variations in soil temperature and moisture [9][10][11][12][13] and physiological aspects of the seeds particularly seed dormancy [14]. When favorable environmental conditions occur and physiological constraints are overcome, seeds germinate; weeds grow and produce new propagules enriching the soil seedbank.…”
Section: Introductionmentioning
confidence: 99%